Influence of working capital management practices on financial performance of small and medium enterprises in Machakos Sub-County, Kenya - Ondieki, Thomas Nyakundi (My University, 2015)
Working capital can be considered as source of existence for all types of organizations, whether profit or non-profit organizations, therefore, it is a vital component for any profit making organizations for it influences operational level and sales volume, The purpose of this study was to assess the influence of Working Capital Management Practices on Financial Performance of SMEs in Machakos Sub-County, Kenya.